RELATIONSHIP BETWEEN MACRONUTRIENT INTAKE AND BLOOD PRESSURE IN HYPERTENSIVE PATIENTS: A CROSS-SECTIONAL STUDY - Anugerah Humairah Z; Shelly Puspa Anggraini; Fina Aryani (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Hypertension remains a global health problem with high prevalence. Lifestyle factors, particularly diet, play an essential role in controlling hypertension. Although there are still conflicting studies, macronutrients (fat, protein, and carbohydrates) have been shown to affect blood pressure and body metabolism. The purpose of this study was to analyze the relationship between blood pressure and macronutrient intake in individuals with hypertension. This study employed a cross-sectional design at the Internal Medicine Clinic of the Pekanbaru Medical Center (PMC) in July and August 2025. A total of 86 outpatients with hypertension were selected as samples using complete sampling techniques. The 2×24-hour dietary recall technique was used to collect data on macronutrient intake, and Spearman's test was applied with systolic and diastolic readings of 148.16±19.21 mmHg and 88.74±10.78 mmHg, respectively, for 12 respondents. The average macronutrient intake was 173±66 g of carbohydrates, 57±24 g of protein, and 61±42 g of fat. There was a significant correlation (p = 0.013) with bivariate analysis, but not with diastolic blood pressure (p = 0.542). Blood pressure measured with a digital sphygmomanometer did not correlate with lipids or carbohydrates. p<0.05 was used for analysis. Protein and systolic blood pressure were found to have a significant correlation with mean macronutrient blood pressure, which includes lipids, protein, and carbohydrates. The conclusion is that systolic blood pressure is influenced by protein intake, whereas carbohydrates and fats do not have a significant effect on it. Monitoring protein intake is a crucial concern in managing the diet of hypertensive patients.